Secured smart ATM transaction - C. R. Balamurugan; K. Ramash kumar; A. Thirumalai (Institute of Advanced Engineering and Science, 2019)
The objective of this paper is to reduce the service tax during mobile transactions. To improve the security and to make the process easy and less time consuming this process is rendered with the help of GSM (Global System for Mobile communication), finger print sensors, PIC16F877A microcontroller and aadhaar number.